Effects of phthalates on normal human breast cells co-cultured with different fibroblasts - Chen, Fang-Ping (PLoS One, 2018)
Whether or not phthalates play a role in breast carcinogenesis remains to be determined. The goal of this study was to explore the effects of phthalates on the growth of normal MCF-10A breast cells modulated by breast fibroblasts. Fibroblasts were derived from normal mammary tissue adjacent to both estrogen receptor (ER) positive and negative primary breast cancers, which were grown separately from nontumorigenic MCF-10A epithelial cells. MCF-10A co-culture cells were treated with 10 nM 17β-estradiol (E(2)), Butyl benzyl phthalate (BBP), di(n-butyl) phthalate (DBP), and di(20ethylhexyl) phthalate (DEHP) (10 and 100 nM). After incubation for 120 hours, the cells were harvested and extracted for MTT assay. Western blot analysis was used to evaluate the proliferative pathway proteins and the effects on ER α. Only fibroblasts from ER (+) breast cancer significantly stimulated proliferation of MCF-10A cells. Exposure of the co-culture to E(2), BBP, DBP, DEHP, and E(2) combined with one of these phthalates resulted in significantly increased cell proliferation, as well as proliferating cell nuclear antigen (PCNA) and ER α expressions. The present study demonstrates that phthalates express a significant influence in fibroblast–epithelial interactions, similarly to the effects of E(2) on breast cells. The effects of phthalates on normal breast cells depend upon ER modulating actions. In breast carcinogenesis, phthalates should be considered as having endocrine disrupting potential, even at low concentrations.